Case report: Ensitrelvir for treatment of persistent COVID-19 in lymphoma patients: a report of two cases - Furuya, Chiho; Yasuda, Hajime; Hiki, Makoto; Shirane, Shuichi; Yamana, Tomohito; Uchimura, Ayana; Inano, Tadaaki; Takaku, Tomoiku; Hamano, Yasuharu; Ando, Miki (Frontiers in Immunology, 2024)
Persistent COVID-19 is a well recognized issues of concern in patients with hematological malignancies. Such patients are not only at risk of mortality due to the infection itself, but are also at risk of suboptimal malignancy-related outcomes because of delays and terminations of chemotherapy. We report two lymphoma patients with heavily pretreated persistent COVID-19 in which ensitrelvir brought about radical changes in the clinical course leading to rapid remissions.Patient 1 was on ibrutinib treatment for mantle cell lymphoma when he developed COVID-19 pneumonia which was severe and ongoing for 2 months despite therapy with molnupiravir, multiple courses of remdesivir, one course of sotrovimab, tocilizumab, and steroids. Patient 2 was administered R-CHOP therapy for diffuse large B-cell lymphoma when he developed COVID-19 which was ongoing for a month despite treatment with multiple courses of remdesivir and one course of sotrovimab. A 5-day administration of ensitrelvir promptly resolved the persistent COVID-19 accommodated by negative conversions of RT-qPCR tests in both patients within days.Ensitrelvir is a novel COVID-19 therapeutic that accelerates viral clearance through inhibition of the main protease of SARS-CoV-2, 3-chymotrypsin-like protease, which is vital for viral replication. Ensitrelvir is a promising treatment approach for immunocompromised lymphoma patients suffering from persisting and severe COVID-19.